2015
DOI: 10.1093/hmg/ddv190
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide association study of toxic metals and trace elements reveals novel associations

Abstract: The accumulation of toxic metals in the human body is influenced by exposure and mechanisms involved in metabolism, some of which may be under genetic control. This is the first genome-wide association study to investigate variants associated with whole blood levels of a range of toxic metals. Eleven toxic metals and trace elements (aluminium, cadmium, cobalt, copper, chromium, mercury, manganese, molybdenum, nickel, lead and zinc) were assayed in a cohort of 949 individuals using mass spectrometry. DNA sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
109
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(116 citation statements)
references
References 54 publications
5
109
2
Order By: Relevance
“…Postnatal dentine showed associations of Mn concentrations with rs1776029 genotypes that are consistent with patterns previously observed in blood of adults where rs1776029 rare allele (A) was associated with higher Mn and rs12064812 rare allele C with lower Mn (Ng et al, 2015; Wahlberg et al, 2016), while for prenatal dentine, the associations were in opposite directions. We hypothesize that this pattern could reflect the new conditions experienced by the child after birth in respect to nutritional uptake and homeostasis.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Postnatal dentine showed associations of Mn concentrations with rs1776029 genotypes that are consistent with patterns previously observed in blood of adults where rs1776029 rare allele (A) was associated with higher Mn and rs12064812 rare allele C with lower Mn (Ng et al, 2015; Wahlberg et al, 2016), while for prenatal dentine, the associations were in opposite directions. We hypothesize that this pattern could reflect the new conditions experienced by the child after birth in respect to nutritional uptake and homeostasis.…”
Section: Discussionsupporting
confidence: 88%
“…In this study we have evaluated three SNPs in Mn transporter Mn transporter genes SLC30A10.... SLC30A10 and SLC39A8 that have previously been shown to have a significant influence on blood Mn concentrations in adults and have also been associated with neurological symptoms (Ng et al, 2015; Pickrell et al, 2016; Wahlberg et al, 2016). This is however the first study evaluating the influence of these SNPs on Mn regulation in early-life human development and we have observed interesting consistent patterns of associations between these SNPs with Mn concentrations in dentine representative of different early life stages.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the possible influence of BMI on ETS intake determined by differences in respiratory rates and respiratory capacities in pediatric age, it should be considered a research agenda of the studies performed in this field. Likewise, since a recent genome-wide association study (Ng et al, 2015) demonstrated a significant relationship between blood levels of several toxic metals and genetic variants in metal transporter genes, future researches should carefully consider also the genetic influence on accumulation of trace elements in the human body and their urinary excretion.…”
Section: Discussionmentioning
confidence: 99%
“…Recent significant findings show that loss-of-function mutations of the ZnT10/SLC30A10 gene result in parkinsonism with hypermanganesemia, a syndrome of hepatic cirrhosis, polycythemia, and dystonia (22,23). ZnT10 is localized to the plasma membrane and is functional in manganese metabolism by effluxing cytosolic manganese (24,25). ZnT10 is also involved in zinc homeostasis in subcellular localization (26,27).…”
mentioning
confidence: 99%